Verification of a Predictive Model of Psychological Health at Work in Canada and France - Jean-Sébastien Boudrias; Patrick Gaudreau; Pascale Desrumaux; Jean-Simon Leclerc; Murielle Ntsame-Sima; André Savoie; Luc Brunet (Psychologica Belgica, 2014)
The purpose of this study was to test the invariance of a predictive model of psychological health at work (PHW) in Canada and France. The model a) defines PHW as an integrative second-order variable (low distress, high well-being) and b) includes three categories of PHW inductors (job demands, personal resources and social-organizational resources) and one psychological intermediate variable (needs satisfaction) that were found to be directly or indirectly related to PHW in a previous study on a sample of French teachers (Boudrias, Desrumaux, Gaudreau, Nelson, Savoie and Brunet, 2011). To test if this model is invariant across countries, these data from French teachers ('N' = 391) were reanalyzed and compared with data from a sample of Canadian teachers ('N' = 480) who completed the same set of questionnaires. Results from structural equation modeling analyses indicated that the model is completely invariant across the two samples. Therefore, pathways to PHW appeared to generalize across these samples of teachers without the addition of other cultural variables. This PHW model suggests that personal resources exert considerable influence directly and indirectly on psychological health through multiple mediators. Research implications and study limitations are discussed.